The Development Prehistoric Of Jember Tourism Module Using Dick And Carey Model - Qoriah, Yaumil; Sumarno, Sumarno; Umamah, Nurul (JURNAL HISTORICA, 2017)
The paradigm change colleges associated with the concept of student centered learning requires the learning process more active learners. Learning components on the concept of student centered learning is the learners and teaching materials. One of the teaching materials is a module. This research aims to develop a Jember Prehistoric Tourism Object Module. The method used Dick and Carey research design. Modules will be tested on 2014 academic year history education students. The data analysis was obtained from expert material validity, expert design and language expert using descriptive method through questionnaire, product effectivity test developed from learning outcome obtained from pretest and posttest. Modul validity result showed that expert material validity was 83%, expert design validity was 87,14%, language expert validity was 81,7%, and product effectivity was 71,2%, that means the product was valid and effective in improving student’s learning outcome. It can be said that Jember prehistorical tourism object module can be used by the students as the media of learning history. Keywords: Module, Dick and Carey Model, validity, effectiveness